Passive social network site use and subjective well-being: A moderated mediation model. (November 2016) - Chen, Wu; Fan, Cui-Ying; Liu, Qin-Xue; Zhou, Zong-Kui; Xie, Xiao-Chun
Abstract: The present study examined whether self-esteem mediated the relationship between passive social network site use (SNS) and subjective well-being, and whether this mediating process was moderated by effortful control. 451 college students (mean age = 21.51 years, SD = 1.47) in Hubei province, China, completed anonymous questionnaires regarding passive SNS use, subjective well-being, self-esteem and effortful control. The results showed that the negative association between passive social network site use and subjective well-being was mediated by self-esteem. Moreover, the mediating effect of self-esteem was moderated by effortful control, with the mediating effect being stronger for individuals with low effortful control than for those with high effortful control. These findings can be beneficial to our understanding of how and when passive SNS use impacts college students' well-being. Highlights: Passive social network site use was negatively associated with subjective well-being. Self-esteem mediated the effect of passive social network site use on subjective well-being. Effortful control moderated the mediation effect of self-esteem.